2009
DOI: 10.1007/s10803-009-0743-2
|View full text |Cite
|
Sign up to set email alerts
|

Using the Autism-Spectrum Quotient to Discriminate Autism Spectrum Disorder from ADHD in Adult Patients With and Without Comorbid Substance Use Disorder

Abstract: It is unknown whether the Autism-spectrum quotient (AQ) can discriminate between Autism Spectrum Disorder (ASD) and Attention Deficit and Hyperactivity Disorder (ADHD) with or without comorbid Substance Use Disorder (SUD). ANOVA's were used to analyse the mean AQ (sub)scores of 129 adults with ASD or ADHD. We applied receiver operating characteristic (ROC) computations to assess discriminant power. All but one of the mean AQ (sub)scores were significantly higher for adults with ASD compared to those with ADHD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 24 publications
4
26
0
1
Order By: Relevance
“…Our findings are also in agreement with the notion that in autism, impairment in Social skill is regarded a primary deficit (Carter et al, 2005) while in schizophrenia this is still unclear (Brü ne, 2005). Similar results were found when ADHD and ASD were compared: social impairment in ASD appears larger than in ADHD (Sizoo et al, 2009). However, research comparing ASD with OCD and SAD yielded mixed results.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Our findings are also in agreement with the notion that in autism, impairment in Social skill is regarded a primary deficit (Carter et al, 2005) while in schizophrenia this is still unclear (Brü ne, 2005). Similar results were found when ADHD and ASD were compared: social impairment in ASD appears larger than in ADHD (Sizoo et al, 2009). However, research comparing ASD with OCD and SAD yielded mixed results.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies reported more impairment in ASD than in ADHD, SAD and OCD in this respect Sizoo et al, 2009). Our findings with respect to the schizophrenia group are in contrast with previous research, which showed enhanced imagination in individuals with schizophrenia (Sacks, van de Ven, Etschenberg, Schatz, & Linden, 2005).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations